Rastros de la esclavitud en la sociedad revolucionaria cubana: la isla según Sara Gómez - Laurence H. Mullaly (Études Caribéennes)
Sara Gómez, the first Afro-Cuban female director, tried to capture and denounce in her movies the forms of power and domination that have become naturalized by the colonial social structures and which, regardless of the fact that the Revolution had declared them obsolete, continue to reproduce themselves and maintain asymetrical relationships in place. De cierta manera (One way or another) brings to the screen and questions from an original perspective the longevity of these ethnical and racial hierarchies, founded on gender and class, in the new Cuban society.